Design- and Theory-Based Approaches to Strategic Decisions - Gambardella, Alfonso; Messinese, Danilo (Organization Science, 2025)
We develop a unified framework to examine the implications of two primary approaches to strategic decision making under uncertainty: designing and shaping future scenarios vis-à-vis testing theories about future scenarios. We conducted a three-arm randomized controlled trial involving 308 early stage entrepreneurs, dividing them into three groups—design-based training, theory-based training, and a control group—and tracked them over approximately 1.5 years. Our findings reveal that both approaches reduce the need for information in decision making and lead to higher commitment rates. The design-based approach encourages action despite negative beliefs, resulting in less frequent and later project termination. In contrast, the theory-based approach promotes a more conservative termination rule, leading to earlier and more frequent project abandonment. Although the theory-based approach is associated with higher average performance upon survival, the design-based approach fosters breakthroughs for decision makers. In sum, the design-based approach is well-suited for innovative ventures that gather information to shape their environment, whereas the theory-based approach is optimal for pursuing high performance under lower degrees of uncertainty. Funding: The research leading to these results has received funding from the Italian Ministry for Education, “Entrepreneurs as Scientists: When and How Start-ups Benefit from a Scientific Approach to Decision Making” project [Grant PRIN 2017, Prot. 2017PM7R52, CUP J44I20000220001]. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2023.18245 .